2001
DOI: 10.1093/ptj/81.9.1502
|View full text |Cite
|
Sign up to set email alerts
|

Level of Activities Associated With Mobility During Everyday Life in Patients With Chronic Congestive Heart Failure as Measured With an “Activity Monitor”

Abstract: Background and Purpose. Because of dyspnea and fatigue, patients with congestive heart failure (CHF) may be restricted in the performance of normal everyday activities. The aim of this study was to obtain a preliminary indication of the level of activities associated with mobility during everyday life and between-day variance in activities in patients with mild to moderate CHF as measured with an “Activity Monitor.” Subjects and Methods. The “Activity Monitor” is based on long-term (>24 hours) ambulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 20 publications
2
33
1
Order By: Relevance
“…This discrepancy between the studies may be explained by the small number of subjects in the pilot study (nϭ5) and by a possible selection bias in both studies. However, in comparison with normative values for the duration of dynamic activities as measured with the AM (Xϭ11.5%, SDϭ3.8%), 1,27,28,42 the mean level of movement-related everyday activity in the present study was low (72% of normative values). When defining hypoactivity as the norm minus 1 standard deviation, more than half of the subjects (nϭ20, 56%) was classified as hypoactive.…”
Section: Generalcontrasting
confidence: 79%
See 3 more Smart Citations
“…This discrepancy between the studies may be explained by the small number of subjects in the pilot study (nϭ5) and by a possible selection bias in both studies. However, in comparison with normative values for the duration of dynamic activities as measured with the AM (Xϭ11.5%, SDϭ3.8%), 1,27,28,42 the mean level of movement-related everyday activity in the present study was low (72% of normative values). When defining hypoactivity as the norm minus 1 standard deviation, more than half of the subjects (nϭ20, 56%) was classified as hypoactive.…”
Section: Generalcontrasting
confidence: 79%
“…As a result, we believe that they may experience diminished function due to a sequence of negative effects: hypoactivity leading to reduced fitness, leading to further hypoactivity. In a previous study, 1 we found that the mean duration that people with CHF performed movement-related activities during a day was considerably lower compared with subjects who were healthy (0.8 versus 2.2 hours per day, respectively; PϽ.05). This hypoactivity in CHF also has been found in other studies [2][3][4][5][6] and may have detrimental effects on fitness, 6 social participation, and prognosis.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…However, exercise protocols involving upper extremity, self-paced walking and trunk muscles activation closely mimic activities of daily living that may be better suited as functional exercises [14]. The appropriate exercise protocols that will serve as the first line of exercise interventions for improving physical function in patients with CHF are still a challenge [15].…”
Section: Introductionmentioning
confidence: 99%